SAR Analysis of Small Molecules Interfering with Energy-Metabolism in Mycobacterium tuberculosis - Federico Appetecchia; Sara Consalvi; Cristina Scarpecci; Mariangela Biava; Giovanna Poce (MDPI AG, 2020)
Tuberculosis remains the world's top infectious killer: it caused a total of 1.5 million deaths and 10 million people fell ill with TB in 2018. Thanks to TB diagnosis and treatment, mortality has been falling in recent years, with an estimated 58 million saved lives between 2000 and 2018. However, the emergence of multidrug-resistant (MDR) and extensively drug-resistant (XDR) Mtb strains is a major concern that might reverse this progress. Therefore, the development of new drugs acting upon novel mechanisms of action is a high priority in the global health agenda. With the approval of bedaquiline, which targets mycobacterial energy production, and delamanid, which targets cell wall synthesis and energy production, the energy-metabolism in Mtb has received much attention in the last decade as a potential target to investigate and develop new antimycobacterial drugs. In this review, we describe potent anti-mycobacterial agents targeting the energy-metabolism at different steps with a special focus on structure-activity relationship (SAR) studies of the most advanced compound classes.